CFD Analysis of Unsteady Yaw Motion of A Towed Ship - Fitriadhy, A.; Mansor, N. Aqilah; Aldin, N. Adlina (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
Instability of a towed ship presented in the form of her unstable yaw motion may lead to serious accident especially at the restricted waterways such as colliding with other ships or onshore structures. To stabilize this unsteady yaw motion, a comprehensive investigation is then required to ensure a safety of ship's towing navigation. This paper presents a computational fluid dynamic (CFD) approach to analyse yaw motion characteristics of a towed ship incorporated with an asymmetrical bridle towline model. Several towing parameters such as towing's angles and speeds have taken into account. Here, a towed ship or barge in then called as 1B is employed in this simulation. The results revealed that the subsequent increase of towing's angle dealt with a better yaw motion of 1B indicated by sufficient reduction of her sway motion associated with more steady yaw motion of a towed ship.